2008
DOI: 10.2172/946677
|View full text |Cite
|
Sign up to set email alerts
|

Cladding embrittlement during postulated loss-of-coolant accidents.

Abstract: The effect of fuel burnup on the embrittlement of various cladding alloys was examined with laboratory tests conducted under conditions relevant to loss-of-coolant accidents (LOCAs). The cladding materials tested were Zircaloy-4, Zircaloy-2, ZIRLO, M5, and E110. Tests were performed with specimens sectioned from as-fabricated cladding, from prehydrided (surrogate for high-burnup) cladding, and from high-burnup fuel rods which had been irradiated in commercial reactors. The tests were designed to determine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(115 citation statements)
references
References 16 publications
5
105
1
Order By: Relevance
“…On the basis of previous observations of the hydrides in high-burnup ZIRLO™ with 300-600 wppm hydrogen [4,9,10], the primary difference in hydride distribution is in the thickness of the outer-surface hydride rim. Hydrides below the rim, particularly within the inner two thirds of the cladding wall, were sparsely distributed circumferential hydrides, and the C H values within this region appeared to be low.…”
Section: As-irradiated High-burnup Zirlomentioning
confidence: 99%
“…On the basis of previous observations of the hydrides in high-burnup ZIRLO™ with 300-600 wppm hydrogen [4,9,10], the primary difference in hydride distribution is in the thickness of the outer-surface hydride rim. Hydrides below the rim, particularly within the inner two thirds of the cladding wall, were sparsely distributed circumferential hydrides, and the C H values within this region appeared to be low.…”
Section: As-irradiated High-burnup Zirlomentioning
confidence: 99%
“…Both segments were sectioned from regions away from grid-spacer locations and within the uniform burnup region of the rod. Extensive characterization of sibling rods irradiated in the same lead test assembly was performed for the NRC-sponsored loss-of-coolant accident (LOCA) research program conducted by Argonne [14]. Based on sibling-rod characterization, the expected corrosion layer thickness (δ ox ) and hydrogen content (C H ) were: (a) 75 µm and 550 wppm for segment 605C6 and (b) 100 µm and 750 wppm for segment 605C2.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the differences in the microstructure, it has been reported that oxidation kinetics, fracture behavior in the LOCA-simulated experiments, and postquench ductility in the ring compression tests are not so sensitive to alloy constituents. 2,6) Therefore, all the examined cladding alloys are not distinguished in the following evaluation.…”
Section: Postquench Ductilitymentioning
confidence: 99%
“…4,5) The tests have recently been performed with prehydrided nonirradiated cladding and high-burnup fuel cladding (70 GWd/t, <700 ppm) in order to confirm the safety of the high-burnup fuel and revise the criteria if necessary. [6][7][8][9][10][11] As a result, hydrogen produced the main burnup effect on embrittlement and the zero-ductility was seen at the oxidations much lower than the safety limit when the cladding absorbed hundreds of ppm of hydrogen, which is inconsistent with the results from the LOCA-simulated experiments.…”
Section: Introductionmentioning
confidence: 99%